Human energy consumption in oil palm loose fruit collection under different terrain conditions: a case study / Mohd Faris Mohd Fauzee - Mohd Fauzee, Mohd Faris (Faculty of Plantation Management and Agrotechnology, 2017)
Oil palm loose fruit collection is always been a topic to be discussed and studied over the recent years, it is either related to mechanization of the task or the field productivity of the task itself. Too common for that loose fruit is left unintended on the ground or rather ineffectively being collected from the soil surface. It is often that workers assigned for the oil palm loose fruit collecting task in plantation complained about the job difficulty due to the various terrains condition that they had to face on. So there is a need to find human energy consumption in relation with different condition of terrain to prove the cases. The objective of this study is to determine the different of human energy used in collecting loose fruit in flat and hilly terrain in the oil palm plantation. Based on the main aim of the study, the parameter of study and the location of study are determined. The location chosen for this study is Ladang Pertubuhan Peladang Negeri Johor (PPNJ) Kahang 2, Johor. The parameters of this study are time, size of plot, number of worker involved and food energy consumption. Together with all of the information, energy is calculated using a human energy calculation formula. The study is then supported with other additional data that would serve as reference information such as rainfall rate, plot productivity, plot related maintenance and workers body mass index (BMI). It have been found that the energy usage of the flat terrain is 1.787 Mega Joules (Mj) per hectare while the hilly terrain human energy consumption consumed as much as 2.722 Mega Joules (Mj) per hectare while the time consumption per hectare is 41.88 minutes and 63.71 minutes per hectare respectively. From the study, we can conclude that the energy usage in the hilly terrain is higher when compare to the flat terrain and by the result achieved it can be used for future references in plantation in meeting the requirement task timeline, by knowing the exact field productivity, plantation management can manage the number worker needed to be assigned to the task so that the daily production requirement can be met.